Locational Dynamics in an Era of Global Economic Change: Is the Port of Rotterdam Up to the Challenge? - Amanda Mackloet (European Regional Science Association (ERSA), 2006)
This paper aims to shed more light on the impact of global economic change on the locational dynamics of maritime firms in the port of Rotterdam, and explores if recent port policy strategies provide an answer to these changes. Globalization and increasing competitiveness have caused a decline in the leading role of the port of Rotterdam. More ports are entering the stage, like the port of Shanghai, which has taken over the lead and is now the biggest port in the world. Also, other inland transport hubs are becoming more and more attractive for the location of port related activities. Furthermore, already for decades the port of Rotterdam faces a loss in employment and added value. The contribution of the port to the Dutch economy is steadily decreasing and causes serious debates about the legitimacy (also in terms of environmental issues) of the port. Firms in the port of Rotterdam have to adapt to the changing global economic playing field and change their strategies. This leads to new dynamics in the location of maritime firms. The paper highlights some developments that indicate changing locational dynamics. For instance, central distribution of consumer goods for the entire European market is likely to change into a decentralised pattern, with regional distribution centres in various countries. Also, the integration of logistics chains has given rise to logistics control functions at high strategic levels, stimulating the need for highly skilled workers and an attractive working environment. The question arises whether the port of Rotterdam is up to the challenge, and can provide an answer to the changing locational dynamics. An outline of the port policy strategy will shed more light on this matter. The cases of the Second Maasvlakte and Stadshavens will provide more insight into future developments.
Keywords: 330